Visualization of the Shape and Colors of the Zytglogge Tower Clock in Evening Party Attire - Sifra Evelyn Parhusip; Cucu Ruhidawati (Universitas Negeri Semarang, 2024)
The Zytglogge Clock Tower is one of the world's heritages with the unique shape of a clock. This study aims to visualize the shape and color of the Zytglogge into a new evening party attire. This Research and Development (RND) used the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). Data were collected using a questionnaire validated by 2 fashion experts. Data were analyzed using quantitative descriptive analysis. All data collected were analyzed using quantitative descriptive analysis techniques. The findings of this research are that it is necessary to add historical elements or background of the idea to add meaning and uniqueness to the outfit, and it is also necessary to pay attention to the materials chosen to realize the design that has been made to get maximum results. Analyzing fashion design principles helps explain the concepts behind evening party dress. Results of evaluation by experts and researchers are beneficial to perfect the party attire.